PENGARUH PEMBELAJARAN MENGGUNAKAN MODEL PETA PIKIRAN (MIND MAPPING) TERHADAP PENINGKATAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA - Fitriana Lestari; Wahyudin Wahyudin; Sufyani Prabawanto (Integral : Pendidikan Matematika, 2019)
This study examines the "Effect of Learning Using a Mind Mapping Model on Improving Students' Mathematical Understanding Ability," with an experimental research method using a pretest-posttest control group design, on a rectangular subject. The object of this experimental research is students of SMP 2 Lembang. The research instrument includes test questions consisting of pretest and posttest questions, which include indicators of students 'mathematical understanding abilities so they can measure comprehension skills, and questionnaires that can read students' responses to the learning model used. The results of the study are based on the preliminary test abilities of the experimental class and the control class the same, after special treatment in the experimental class that is the learning 60 process using a mind map model, while the control class does not get special treatment using only conventional learning, the average results of the post the experimental class was 29.77 while the control class was 25.81. For the average gain index value of the experimental class 0.615 while the average gain index value of the control class 0.403. From the average results of the posttest, it can be seen that the mathematical understanding ability of the experimental students is better than the control students, as for the improvement criteria based on the average gain index of the experimental class the increase is higher than the control class.Keywords: Mathematical understanding, mind map models, conventional